PML/PBL: A new generalized monitor of atmospheric turbulence profiles - Ziad, Aziz; Blary, Flavien; Borgnino, Julien; Fanteï-Caujolle, Yan; Aristidi, Eric; Martin, François; Lanteri, Henri; Douet, Richard; Bondoux, Erick; Mékarnia, Djamel (CCSD, 2013)
International audience The futures large telescopes will be certainly equipped with Multi-Conjugate Adaptive Optics systems. The optimization of the performances of these techniques requires a precise specification of the different components of these systems. Major of these technical specifications are related to the atmospheric turbulence particularly the structure constante of the refractive index Cn2(h) and the outer scale L0(h). New techniques based on the moon limb observation for the monitoring of the Cn2(h) and L0(h) profiles with high vertical resolution will be presented. A new monitor PBL (Profileur Bord Lunaire) for the extraction of the Cn2(h) profile with high vertical resolution has been developed. This instrument uses an optical method based on observation of the moon limb with a DIMM configuration (Differential Image Motion Monitor). Indeed, in the PBL the lunar limb is observed through two sub-apertures of 6cm separated by a base of ~30cm. The moon limb offers a continuum of stars at different angular separations allowing the scan the atmosphere with a very high resolution. The angular correlation along the lunar limb between of the differential distance between the two images of the lunar edge leads to the Cn2(h) profile. The other parameters of turbulence are also accessible from this instrument as the profile of outer scale, the seeing and isoplanatic & isopistonicdomains. The PBL succeeded to our first moon limb profiler MOSP (Monitor of Outer Scale Profile) which was developed mainly for outer scale profile extraction. Several campaigns have been carried out with MOSP particularly at Mauna Kea Observatory (Hawaii) and Cerro Paranal in Chile. The PBL instrument has been installed at Dome C in Antarctica since January 2011. In addition to this winterized PBL for Dome C, a second copy of this instrument has been developed for mid-latitude sites. A first campaign with this light version of PBL, was carried out at the South African Large Telescope (SALT) Observatory in August 2011.